2015
DOI: 10.4049/jimmunol.1401867
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Jak/STAT Signaling in Immunity and Disease

Abstract: More than 2 decades ago, experiments on the antiviral mechanisms of interferons led to the discovery of Janus kinases (JAK) and their downstream effectors, the signal transducer of activation (STAT) proteins. This pathway has since become a paradigm for membrane to nucleus signaling and has come to explain how a broad range of soluble factors, including cytokines and hormones, mediate their diverse functions. Jak/STAT research has not only impacted basic science, particularly in the context of intercellular co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
358
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 451 publications
(388 citation statements)
references
References 81 publications
6
358
0
5
Order By: Relevance
“…An additional level of complexity in the JAK-controlled network is that signals from most cytokines involve two different JAKs (3). It is usually unclear whether both JAKs contribute, or whether each has distinct signaling and transcriptomic consequences (for instance, by triggering parallel signaling pathways) (19,20). We addressed this question using the response of NK cells to IL-2 as a model.…”
Section: Resultsmentioning
confidence: 99%
“…An additional level of complexity in the JAK-controlled network is that signals from most cytokines involve two different JAKs (3). It is usually unclear whether both JAKs contribute, or whether each has distinct signaling and transcriptomic consequences (for instance, by triggering parallel signaling pathways) (19,20). We addressed this question using the response of NK cells to IL-2 as a model.…”
Section: Resultsmentioning
confidence: 99%
“…10 Based on their essential roles in transmitting cytokine-induced signals, the JAKs have become a target for pharmacologic manipulation in inflammatory diseases. [11][12][13] Accordingly, studies have shown that JAK inhibition reduces the signs and symptoms of rheumatoid arthritis and ulcerative colitis, 14,15 as well as the myeloproliferative disorders. 16,17 Given the efficacy of JAK inhibition in these other conditions, we hypothesized that JAK inhibition might serve as a valid therapeutic approach in HLH.…”
Section: Introductionmentioning
confidence: 99%
“…Cytokines signal through STATs, and the modulation of the expression levels of these transcription factors may induce qualitative changes in the T cell response to cytokines (32,33). IL-7 is reported to signal primarily through STAT5.…”
Section: Il-7 Induces Expression and Activation Of Stat1mentioning
confidence: 99%
“…Interestingly, STAT1, IFNG, IRF7, and IFNA were also noted among the top 15 best-scoring upstream regulators ( Figure 3B). To analyze the potential contribu-tion of IL-7-dependent STAT1 activation, we next compared the genes regulated upon IFN-γ stimulation (STAT1-dependent) (33). A direct comparison of the sets of DEGs for IL-7 and IFN-γ stimulation revealed a relatively small overlap in CD4 + and CD8 + naive T cells (n = 63 and n = 70 genes, respectively) ( Figure 3C, Table 2 and Supplemental Table 1; supplemental material available online with this article; https://doi.…”
Section: Il-7 Induces a Set Of Stat1/ifn-associated Genes In Naive T mentioning
confidence: 99%